2013
DOI: 10.1302/0301-620x.95b10.31740
|View full text |Cite
|
Sign up to set email alerts
|

Endoprosthetic replacement after extra-articular resection of bone and soft-tissue tumours around the knee

Abstract: We evaluated the clinical results and complications after extra-articular resection of the distal femur and/or proximal tibia and reconstruction with a tumour endoprosthesis (MUTARS) in 59 patients (mean age 33 years (11 to 74)) with malignant bone or soft-tissue tumours. According to a Kaplan-Meier analysis, limb survival was 76% (95% confidence interval (CI) 64.1 to 88.5) after a mean follow-up of 4.7 years (one month to 17 years). Peri-prosthetic infection was the most common indication for subsequent amput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 24 publications
1
59
0
4
Order By: Relevance
“…Limb salvage after extra-articular resection with an EPR reconstruction can achieve good functional results in most patients, although the rates of complications and subsequent amputation are higher than in patients treated with intra-articular resection. 8 Our results suggest that there is no difference between IAR and EAR functional results in terms of MSTS functional scores but EAR patients developed a higher rate of complications. 8,9,15 Survival curve distribution for limb salvage procedure survival showed that EAR reconstruction were associated with a higher risk of failure in the first 5 years but reconstruction survival results for long terms follow-up presented no significant differences between the two groups.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Limb salvage after extra-articular resection with an EPR reconstruction can achieve good functional results in most patients, although the rates of complications and subsequent amputation are higher than in patients treated with intra-articular resection. 8 Our results suggest that there is no difference between IAR and EAR functional results in terms of MSTS functional scores but EAR patients developed a higher rate of complications. 8,9,15 Survival curve distribution for limb salvage procedure survival showed that EAR reconstruction were associated with a higher risk of failure in the first 5 years but reconstruction survival results for long terms follow-up presented no significant differences between the two groups.…”
Section: Discussionmentioning
confidence: 50%
“…12,13 On the other hand, patients selected for EAR are those with obvious tumour invasion of the joint, iatrogenic contamination due to biopsy, or a pathological fracture with intraarticular extension. 8,9 Neurovascular involvement is an indication for amputation or rotationplasty. 14 There is uncertainty about those patients with suspicion of intraarticular extension of the tumour not clearly proven by preoperative imaging studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original technique was described by the authors in a previous report [5]. Hardes et al [20] described 59 cases of prosthetic reconstructions after extraarticular resection of the knee preserving the extensor apparatus (patellar-split technique), reporting an implant survival rate of 48% at 2 years and 25% at 5 years; the most frequent complication was deep infection, observed in 37% of cases. Ten patients (16.9%) lost their limb as a result of complications.…”
Section: Discussionmentioning
confidence: 99%
“…The authors specifically mentioned a 51% revision rate, but did not attribute this to sports activities. Revisions were performed for soft tissue failure in eight patients, aseptic loosening of the press fit In a previously published study, Hardes et al [1] analyzed 59 patients with a mean followup time of 4.7 years. The authors found worn bearings in 20% of their patient group and periprosthetic fractures in 6% of the patient population.…”
mentioning
confidence: 99%